Primary Otomycosis in the Indian Subcontinent: Predisposing Factors, Microbiology, and Classification - Sampath Chandra Prasad; Subbannayya Kotigadde; Manisha Shekhar; Nikhil Dinaker Thada; Prashanth Prabhu; Tina D’ Souza; Kishore Chandra Prasad (International Journal of Microbiology)
Objective. To define otomycosis and determine the predisposing factors and microbiology in primary otomycosis. Study Design. Prospective study of two years and review of the literature. Setting. Academic Department of Otolaryngology in a coastal city in India. Patients. 150 immunocompetent individuals of whom 100 consecutive patients with a clinical diagnosis of otomycosis are considered as the study group and 50 consecutive patients with no otomycosis are considered as the control group. Results and Observations. Instillation of coconut oil (42%), use of topical antibiotic eardrops (20%), and compulsive cleaning of external ear with hard objects (32%) appeared to be the main predisposing factors in otomycosis. Aspergilli were the most common isolates (80%) followed by Penicillium (8%), Candida albicans (4%), Rhizopus (1%), and Chrysosporium (1%), the last being reported for the first time in otomycosis. Among aspergilli, A. niger complex (38%) was the most common followed by A. fumigatus complex (27%) and A. flavus complex (15%). Bacterial isolates associated with fungi in otomycosis were S. aureus, P. aeruginosa, and Proteus spp. In 42% of healthy external ears fungi were isolated. Conclusion. Aspergillus spp. were the most common fungi isolated, followed by Penicillium. Otomycotic ears are often associated with bacterial isolates when compared to normal ears. Fungi are also present in a significant number of healthy external auditory canals and their profiles match those in cases of otomycosis. The use of terms “primary” and “secondary” otomycosis is important to standardize reporting.